Penile Fracture Due to Manipulation - Alam, KABM Taiful; Islam, Md Sayedul; Haque, Toufiqul; Hossain, Shamim; Islam, Tazul; Rashid, Humayun; Rahman, Md Atiqur (Journal of Surgical Sciences, 2013)
A 24 year old young patient presented in the emergency department of Shaheed Monsur Ali Medical College Hospital, Uttara, Dhaka with swollen, curved and flaccid penis after forceful bending of his erect penis. The patient was anxious with normal vital sign. Rolling sign was positive. There was no bleeding at external urethral orifice, scrotum & testicle were found normal. On the above facts, penile fracture was diagnosed clinically. The penis was degloved upto the root of the penis & after evacuation of the haematomas, transverse tears were detected in Bucks fascia & tunica albugenia of the left corpus cavernosum, which were repaired by interrupted suture. In the post operative period sedative was given & recovery was uneventful. The aim of this case report is to increase the awareness of the condition which should be regarded seriously and treated expeditiously and to draw attention to its possible complications. DOI: http://dx.doi.org/10.3329/jss.v16i1.14448 Journal of Surgical Sciences (2012) Vol. 16 (1) : 44-46